HUBUNGAN PITC ( PROVIDER INITIATED TESTING AND COUNSELING ) OLEH BIDAN KIA/KB DENGAN PENGETAHUAN IBU HAMIL TENTANG PPIA ( PENCEGAHAN PENULARAN HIV DARI IBU KE ANAK ) DI WILAYAH KERJA PUSKESMAS BRATI - Desiliana Puji Andari; Nur Khafidhoh; Ulfah Musdalifah (Midwifery Care Journal, 2020)
Pregnant women are one of the key populations who have the risk of comparative HIV/AIDS to the fetus it contains. Such as transmission can occur during pregnancy, childbirth, and lactation. In Grobogan district there was always a baby or child with HIV possitive in every year. Therefore, the policy arises that every pregnant woman must be examined by HIV. The examination was named PITC (Provider Initiated Testing and Counseling).PITC colaborated with ANC (Ante Natal Care) in Primary Health Center. The purpose of this study is to know the relationship of PITC (Provider Initiated Testing and Counseling) by Midwife KIA/KB with the knowledge of pregnant women about PPIA in the work area of Brati Primary Health Center. This type of this research is correlative analytic with a cross-sectional approach. The method of this research used questionnaires. The samples in this study around 56 pregnant mothers who tested HIV in Brati Puskesmas. Sampling techniques using Accidental sampling were incidentally met by researchers. And data analysis bivariateused Chi-Square. The results of statistical analysis with Chi-Square get p-value of 0.032 0.05. Ha received that there was a relationship between PITC (Provider Initiated Testing and Counseling) by midwife KIA/KB with the knowledge of pregnant women about PPIA. Based on the results this research is expected to midwife KIA/KB in Brati Primary Health Center more improve the quality of service PITC.Because the PITC given by midwives affects the knowledge of pregnant women